Représentations de l'accueil et de l'Humanitaire dans les sites internet des organisations transnationales, nationales et locales reliées à l'intervention auprès des réfugiés - Saillant, Francine; Cogent, Marguerite; Richardson, Mary (Anthropologica, 2022)
This article sets forth an analysis of discourse concerning humanitarianism and refugees, based on a selection of the Internet sites of transnational, national (Canadian) and local (Quebecois) organizations whose action is to a significant degree focussed on refugees themselves. The authors propose to cover both the transnational and the local as they search key texts in these sites for the terms for refugee status, humanitarianism, community and citizenship, and try to apprehend the shifts of meaning and movements of de-territorialization and re-territorialization. Our findings enable us to accomplish the deconstruction of these terms as well as their localization in the core of each one of these sites. The vision of humanitarian action which emerges from our analysis is one which puts its universality in question at the same time that it stimulates us to develop our perspective on localized concepts and their various significations, including those which emanate from transnational organizations.